The Little Data Book 2003 - World Bank (Washington, DC, 2013)
The Little Data Book 2003 is a pocket edition of the World Development Indicators. It is intended as a quick reference for users of the World Development Indicators 2003 book and CD-ROM, the World Bank Atlas, and WDI Online, our new electronic subscription database, which between them cover more than 600 indicators and span 40 years. The 207 country pages in The Little Data Book present the latest available data for World Bank member countries, and other economies with populations of more than 30,000. The 14 summary pages cover regional and income group aggregates. The selection of indicators in these pages have been updated this year to include some of those being used to monitor progress towards the Millennium Development Goals.